The Influence of Sharia-Based Compensation Management and Reward System on Job Satisfaction and Employee Performance - Hermawan, Endang; Setiawan, Aris; Adham, Ibnu; Fakih, Choerul (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2026)
This research investigates the influence of Sharia-based compensation management and reward systems on employee performance and job satisfaction at Bank Perkreditan Syariah At Taqwa Tangerang. A quantitative approach was employed using the census method, gathering data from all 85 employees across various organizational levels and functional departments through structured questionnaires measured on a five-point Likert scale. Data analysis utilized Structural Equation Modeling with the Partial Least Squares approach to examine direct relationships and mediation effects. The findings reveal that Sharia-based compensation management significantly influences both employee performance and job satisfaction. In contrast, Sharia-based reward systems similarly demonstrate a significant positive impact on both outcome variables. Job satisfaction is an important predictor of employee performance and serves as a partial mediator in the relationships among compensation, reward systems, and performance. The integrated model explains substantial variance in job satisfaction and employee performance, confirming that human resource practices grounded in Islamic principles of justice, transparency, and Sharia compliance constitute fundamental drivers of employee outcomes in Islamic microfinance institutions. The research validates that compensation systems that address both material adequacy and spiritual authenticity, combined with reward mechanisms that integrate material recognition and spiritual development opportunities, generate superior motivational effects compared to conventional approaches that emphasize purely economic considerations.